THE CLASSROOM INVERTED IN THE TEACHING-LEARNING PROCESS OF NATURAL SCIENCES IN TIMES OF COVID-19 - Author; Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The health pandemic, product of Covid19, is one of the most worrying crises that it is going through Humanity, in addition to being a health crisis, is also economic and social, leading the inhabitants to implement new lifestyles; that analyzed from the perspective of positivism has generated changes in some sectors that are necessary for the development of the country. Migrating to a virtualized teaching and learning methodology has meant a real challenge for teachers, students, parents and advances for the education sector. This research analyzes the inverted classroom in the teaching-learning process in Natural Sciences, using field, bibliographic and descriptive research, detecting that this method was widely used in higher education; but in primary school education it was very little explored, a survey was applied that was useful to collect relevant information on the advantages, disadvantages and limitations of this teaching method, information that was represented and analyzed in statistical graphics. Connectivity, the main problem evidenced, because a large part of Ecuadorian families do not have access to technological means or internet availability, either due to limited economic resources or because they live in rural areas where there is no coverage, requiring the government to invest more in technology, education and being prepared for any emergent and unforeseen in time.